2023
DOI: 10.7717/peerj.15304
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of pellicle-forming ability in clinical carbapenem-resistant Acinetobacter baumannii

Abstract: Background Acinetobacter baumannii was reported to have resistance towards carbapenems and the ability to form an air-liquid biofilm (pellicle) which contributes to their virulence. The GacSA two-component system has been previously shown to play a role in pellicle formation. Therefore, this study aims to detect the presence of gacA and gacS genes in carbapenem-resistant Acinetobacter baumannii (CRAB) isolates recovered from patients in intensive care units and to investigate their pellicle form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The clinical CRAB strains used in this study, including 3 pellicle-forming strains: AB21 (bronchoalveolar lavage), AB34 (sputum), and AB69 (tracheal secretion), and 3 nonpellicle-forming strains: AB11, AB20, and AB31, were recovered from sputum. The pellicleforming ability of these strains was confirmed through a pellicle formation assay and impedance-based xCELLigence real-time cell analysis using an Agilent xCELLigence system (Agilent, Santa Clara, CA, USA) [20].…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical CRAB strains used in this study, including 3 pellicle-forming strains: AB21 (bronchoalveolar lavage), AB34 (sputum), and AB69 (tracheal secretion), and 3 nonpellicle-forming strains: AB11, AB20, and AB31, were recovered from sputum. The pellicleforming ability of these strains was confirmed through a pellicle formation assay and impedance-based xCELLigence real-time cell analysis using an Agilent xCELLigence system (Agilent, Santa Clara, CA, USA) [20].…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…Building upon our previous study, which identified the rare phenotypic trait of pellicle formation in clinical CRAB isolates collected from the intensive care units of the University Malaya Medical Centre. These isolates could be more virulent as they produced robust biomass in Mueller-Hinton broth with OD 570 ranging from 1.689 ± 0.180 to 3.203 ± 0.569 [20]. Therefore, we aim to delve into the molecular mechanisms underlying the pathogenesis of these pellicle-forming isolates.…”
Section: Introductionmentioning
confidence: 99%